2023
DOI: 10.7199/ped.oncall.2023.31
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged fever, pancytopenia, and splenomegaly - is it sarcoidosis?

Abstract: Childhood Sarcoidosis is a chronic multisystem pinflammatory disease of unknown etiology. We report a case of a 9-year-old female who presented with nasal bleeding. She started with fever that persisted for 24 days associated with progressive splenomegaly, pancytopenia, and generalized lymphadenopathy. An extensive investigation was performed excluding infectious, neoplastic, autoimmune and immunodeficiency causes. Histological examination of a lymph node revealed multiple non-caseous granulomas, which togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The same is true for long-term fever, asthenia or weight loss [8]. Long-term fever was the mode of revelation of sarcoidosis in the studies by Matsuda et al [9], de Gonçalves et al [10], Thomas et al [11] and Kamath et al [12]. In the study Wang et al [13], longterm fever and weight loss were observed respectively in 22.5% and 16.25% of subjects followed for sarcoidosis.…”
Section: Discussionmentioning
confidence: 97%
“…The same is true for long-term fever, asthenia or weight loss [8]. Long-term fever was the mode of revelation of sarcoidosis in the studies by Matsuda et al [9], de Gonçalves et al [10], Thomas et al [11] and Kamath et al [12]. In the study Wang et al [13], longterm fever and weight loss were observed respectively in 22.5% and 16.25% of subjects followed for sarcoidosis.…”
Section: Discussionmentioning
confidence: 97%